Analisis Kepemimpinan Transformasional dan Kepuasan Kerja terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening - Supriadi, Endang Supriadi; Suyanto, Suyanto Suyanto (Innovative: Journal Of Social Science Research, 2025)
This study examines the influence of transformational leadership and job satisfaction on employee performance, with motivation as a mediator, in government bureaucratic reform. Driven by the inconsistency of the study and the ASN performance target, this quantitative study analyzed the data of 91 respondents using Smart PLS V4. Results show transformational leadership and job satisfaction significantly affect motivation. Transformational leadership also positively affects performance. Interestingly, job satisfaction does not directly affect performance, but motivation has been shown to significantly mediate the influence of transformational leadership and fully mediate the influence of job satisfaction on performance. It was found that the crucial role of motivation in improving performance and leadership alignment, contributing to the knowledge of public sector human resources